Expression of sex-related genes and effects of dmrt1 siRNA-silencing on sex differentiation in juvenile yellow perch - Ding-Kun Xie; Han-Ping Wang; Rafidah Othman; Hong Yao; Paul O’Bryant; Dean Rapp (Aquaculture Reports)
In this study, we first sequenced the entire genome of the yellow perch (YP) and screened transcripts of gonadal, liver and brain tissues from fish of different sexes. By comparing known sex-related genes in fish such as dmrt1 and cyp19a1 with YP genome, we obtained full-length sequences through genomic homology analysis. Then an experiment was conducted to determine the effects of dmrt1 siRNA-silencing on sex differentiation of juvenile YP. Transcriptome analysis showed that dmrt1 were mainly expressed in gonad tissue with their levels being significantly higher in the male groups respectively comparing to each other; foxl2 was dominantly expressed in gonads showing a significantly higher expression in big female groups than the male and small female groups. cyp19a1 was dominantly expressed in gonads, while cyp19a2 was dominantly expressed in brain, and both female groups exhibiting a significantly higher expression than the male groups. sox9a was mainly expressed in brain and gonad tissue with the male groups displaying a significantly higher expression in gonad than the female groups. For the dmrt1-siRNA interference experiment, a partial feminization of all-male fish was achieved despite administering the injection at a later stage of sex differentiation. The results showed that the dmrt1 gene interference led to an 20 % increase in the female number and larger size in both males and females compared to the control group. The percentage of females in the experimental group significantly increased to 70.09 %, compared to the 46.79 % in the negative control group. The interference also exerted a detrimental effect on the process of sperm production and maturation. The expression level of dmrt1 exhibited positive and negative correlations with body size of females and males, respectively. These findings suggest that dmrt1 plays a crucial role directly or indirectly in the sex differentiation and growth regulation of YP.